Functional neuroimaging of human vocalizations and affective speech. Issue 6 (December 2014) - Frühholz, Sascha; Sander, David; Grandjean, Didier
Abstract: Neuroimaging studies have verified the important integrative role of the basal ganglia during affective vocalizations. They, however, also point to additional regions supporting vocal monitoring, auditory–motor feedback processing, and online adjustments of vocal motor responses. For the case of affective vocalizations, we suggest partly extending the model to fully consider the link between primate-general and human-specific neural components.